2019
DOI: 10.15174/au.2019.2468
|View full text |Cite
|
Sign up to set email alerts
|

Factores que influyen en la conducta sexual en mujeres nahuas de Puebla, México

Abstract: Las mujeres indígenas son una población vulnerable que experimenta múltiples formas de discriminación e invisibilidad. El objetivo de este estudio fue determinar si la edad del inicio de la vida sexual, escolaridad, conocimientos sobre VIH, SIDA y otras infecciones de transmisión sexual, beneficios, barreras y autoeficacia percibida para el uso del condón y violencia de pareja influyen en la conducta sexual; de las mujeres nahuas de Puebla, México. Se trata de un estudio descriptivo, correlacional transversal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Resultados: la presencia de sífilis se asoció con consumo de alcohol (p<0,001), el sexo transaccional (p=0,010) y la no utilización del condón (p<0,001). Nava Navarro et al (17) Población de estudio: mujeres nahuas de Puebla, México. Resultados: la práctica cultural elimina la posibilidad de negociación para el uso del condón, limitando el ejercicio de los derechos sexuales.…”
Section: Fuente Población Y Resultadosunclassified
“…Resultados: la presencia de sífilis se asoció con consumo de alcohol (p<0,001), el sexo transaccional (p=0,010) y la no utilización del condón (p<0,001). Nava Navarro et al (17) Población de estudio: mujeres nahuas de Puebla, México. Resultados: la práctica cultural elimina la posibilidad de negociación para el uso del condón, limitando el ejercicio de los derechos sexuales.…”
Section: Fuente Población Y Resultadosunclassified
“…This result is congruent with that reported by Meneses-Tirado and collaborators [5], who detailed in a model that adolescents who showed greater commitment to their ethnic group were less likely to have sexual intercourse, and that ethnic identity was a protective factor for safe sex, for a lower number of sexual partners, and for proposing the first sexual relation. However, Nava-Navarro et al [6] and Bukuluki et al [7] reported that greater ethnic identity increased the likelihood of STI presentation. The disparate findings in these studies may be due to inclusion of adults in the study samples.…”
Section: Discussionmentioning
confidence: 99%
“…2 of 11 of capacity to negotiate CU, yet men may designate women as responsible for use of contraceptive methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…This result is congruent with that reported by Meneses-Tirado and collaborators [ 5 ], who detailed in a model that adolescents who showed greater commitment to their ethnic group were less likely to have sexual intercourse, and that ethnic identity was a protective factor for safe sex, for a lower number of sexual partners, and for proposing the first sexual relation. However, Nava-Navarro et al [ 6 ] and Bukuluki et al [ 7 ] reported that greater ethnic identity value increased the likelihood of STI presentation. The disparate findings in these studies may be due to inclusion of adults in the study samples.…”
Section: Discussionmentioning
confidence: 99%
“…They also have difficulty with correct condom use such as placement of condoms on their partners. This implies the lack of ability to negotiate CU, yet men may designate women as responsible for use of contraceptive methods [ 6 ].…”
Section: Introductionmentioning
confidence: 99%